PENEGAKAN HUKUM TERHADAP TINDAK PIDANA CYBER DI WILAYAH HUKUM POLDA JATENG - yusrina; dio; Sitta Saraya (Fakultas Hukum Universitas Selamat Sri, 2023)
The development of science and technology encourages the use of Information Technology, media and communication which has changed the behavior of society and human civilization globally and worldwide. The development of information and communication technology has also made world relations borderless and caused significant social, economic and cultural changes to take place so quickly. Information Technology today is like a coin that we can see from both sides because apart from contributing to the improvement of human welfare, progress and civilization, as well as being an effective tool for acts against the law, of course, it often brings negative impacts, this cannot be separated from both sides of the eye. the coins, but that does not mean that illegal acts will stick with technological developments. People often use computers as a tool to commit crimes, and the development of technology now that smartphones can also be used as tools and through social media applications and other applications can be used as an opportunity to commit crimes. This writing was carried out with a sociological juridical review by conducting research and supported by data, both laws and appropriate reference books. This study aims to determine the enforcement of criminal law against cyber crimes in the Legal Area of ​​the Central Java Regional Police and what obstacles and obstacles are faced in enforcing cyber crimes